The effects of somatostatin analogues on glycaemia in the treatment of neuroendocrine tumours. (25th January 2022) - Patel, Kishen Rajan; Nahar, Ananda; Elhassan, Yasir S.; Shetty, Shishir; Smith, Stacey; Vickrage, Suzanne; Kemp‐Blake, Joanne; Palani, Raghavendar; Geh, Ian; Venkataraman, Hema; Shah, Tahir; Ayuk, John
Abstract: Long‐acting somatostatin analogues (SSAs) are the most commonly used drugs in the management of neuroendocrine tumours (NETs) because of their ability to control symptoms and prolong survival. SSA use is associated with changes in glucose metabolism. However, the impacts on glycaemic control and body mass index (BMI) caused by SSAs in NETs are largely unknown. In the present study, we evaluated the effects of SSA treatment on BMI and glycated haemoglobin (HbA1c) in our cohort of patients with NETs. We also assessed changes in glycaemic control and BMI before and after SSA treatment. In addition, we assessed the incidence of new diabetes or whether there was worsening of glycaemic control for patients with pre‐existing diabetes. The study comprised a retrospective study of 279 patients with NETs who were treated with SSAs between January 2014 and January 2019. Glycaemic control was assessed by measuring changes in Hba1c. A number needed to harm analysis was used to look at new cases of diabetes within the study population. Treatment with SSAs was associated with a mean increase in HbA1c of 3.35 ± 6.30 mmol mol –1 despite a mean decrease in BMI of −1.04 ± 2.79 kg m –2 . There were 19 new cases of type 2 diabetes mellitus (T2DM) in the population of 209 with a number needed to harm of 12.5. Of the 34 patients with pre‐existing T2DM, five had worsening of their mean HbA1c. Treatment with SSAs for NETs is associated with an increase in HbA1c, despite a reduction in BMI and, importantly, a risk of developing T2DM with a number needed to harm of 12.5. This project was registered with the National Health Service Clinical Audit and Registries. It has a CARMS number ‐ 17666. Abstract : The effects of somatostatin analogues on glycaemia in the treatment of neuroendocrine tumours.